2008
DOI: 10.1021/cg7010293
|View full text |Cite
|
Sign up to set email alerts
|

The N—H···X (X = Cl, Br, and I) Hydrogen-Bonding Pattern in Aromatic Amides: A Crystallographic and 1H NMR Study

Abstract: This paper addresses the stability of the intramolecular five-and six-membered NsH • • • X (X ) Cl, Br, and I) hydrogen bonds in aromatic amides. The crystal structures of 11 chloro-, bromo-, or iodo-substituted aromatic amides are reported. It is revealed that five-membered NsH • • • X hydrogen bonding occurs for all the halogen atoms in the designed compounds. Introduction of a large aryl or alkyl unit increases the stability of the hydrogen bonding because its existence weakens the competitive intermolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 76 publications
2
22
0
1
Order By: Relevance
“…In contrast, there is a deficiency of NMR studies on HBing to weak organic halogen acceptors. 97 Chemical shift analysis and H/D exchange experiments on this system support that intramolecular HBing occurs in G2XB . The NH 2 1 H NMR resonance in G2XB was shifted downfield by 0.52 ppm (5.30 ppm, CDCl 3 ) as compared to G2HB (4.78 ppm, CDCl 3 ).…”
Section: Resultsmentioning
confidence: 63%
“…In contrast, there is a deficiency of NMR studies on HBing to weak organic halogen acceptors. 97 Chemical shift analysis and H/D exchange experiments on this system support that intramolecular HBing occurs in G2XB . The NH 2 1 H NMR resonance in G2XB was shifted downfield by 0.52 ppm (5.30 ppm, CDCl 3 ) as compared to G2HB (4.78 ppm, CDCl 3 ).…”
Section: Resultsmentioning
confidence: 63%
“…A trityl group flanking the amide proton provided sufficient steric hindrance to prevent intermolecular hydrogen bonding. The effectiveness of this functional group arrangement has been described in several reports by Li and co‐workers, who noted that five‐membered N−H⋅⋅⋅X (X=Cl, Br, I) hydrogen bonding rings were more stable than six‐membered rings in aromatic amides [42–44] . A charge‐assisted C−H hydrogen bond donor ortho to the amide substituent was designed to reduce conformational flexibility by intramolecular hydrogen bonding to the amide carbonyl oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for the discrepancy in hydrogen bonding distance results from the increased acidity (increased donor ability) of the 2aminopyridyl ligand. [36][37][38] In addition, weak interaction studies reveal the presence of various CH...Cl, CH...π, π...π interactions in the solid state. Interestingly, in complex 3 it is observed that distances between CH...Cl, CH...π, π...π are 2.71-2.84, 2.58-2.83 and 3.83-3.84 Å, respectively and result in a grid 2D sheet Complex 4 shows distances between CH...Cl, π...π as 2.71-2.84, 3.83-3.84 Å, respectively and result in a grid 2D sheet but without CH...π interaction.…”
Section: Synthesis Of the Complexesmentioning
confidence: 99%